Manipulation of interrenal cell function in developing zebrafish using genetically targeted ablation and an optogenetic tool - Gutiérrez Triana, José Arturo; Herget, Ulrich; Castillo-Ramirez, Luis Alberto; Lutz, Markus; Yeh, Chen-Min; De Marco, Rodrigo J.; Ryu, Soojin (Endocrinology, 2015)
Zebrafish offer an opportunity to study conserved mechanisms underlying the ontogeny and physiology of the hypothalamic-pituitary-adrenal/interrenal axis. As the final effector of the hypothalamic-pituitary-adrenal/interrenal axis, glucocorticoids exert both rapid and long-term regulatory functions. To elucidate their specific effects in zebrafish, transgenic approaches are necessary to complement pharmacological studies. Here, we report a robust approach to specifically manipulate endogenous concentrations of cortisol by targeting heterologous proteins to interrenal cells using a promoter element of the steroidogenic acute regulatory protein. To test this approach, we first used this regulatory region to generate a transgenic line expressing the bacterial nitroreductase protein, which allows conditional targeted ablation of interrenal cells. We demonstrate that this line can be used to specifically ablate interrenal cells, drastically reducing both basal and stress-induced cortisol concentrations. Next, we coupled this regulatory region to an optogenetic actuator, Beggiatoa photoactivated adenylyl cyclase, to increase endogenous cortisol concentrations in a blue light-dependent manner. Thus, our approach allows specific manipulations of steroidogenic interrenal cell activity for studying the effects of both hypo- and hypercortisolemia in zebrafish.
Gesehen am 04.02.2021